A mutant variant of Nix gene on ?-irradiated Aedes aegypti as a male-determination factor - BENI ERNAWAN; HARRY NUGROHO EKO SURNIYANTORO; IRAWAN SUGORO; USMAN SUMO FRIEND TAMBUNAN (Society for Indonesian Biodiversity, 2019)
Abstract. Ernawan B, Surniyantoro HNE, Sugoro I, Tambunan USF. 2019. A mutant variant of Nix gene on ?-irradiated Aedes aegypti as a male-determination factor. Biodiversitas 20: 893-899. This study was aimed to examine the effect of ?-irradiation on the Nix gene sequence as a male-determination factor on Ae. aegypti. The novelty of the present study is the investigation on the gene mutation level of the deoxyribonucleic acid as an impact of ionizing radiation exposure. Males Ae. aegypti at the pupal stage were sterilized by applying 70 Gy ?-rays in varies dose-rates, i.e., 300, 600, 900, 1200 and 1500 Gy/h utilizing panoramic irradiator and males group without ?-irradiation as controls. Adult males that emerged from the pupal stage were assessed for the Nix gene sequence using a Real-Time Polymerase Chain Reaction method and were sequenced using Clustal Omega and Bioedit software, respectively. The results indicated that mutation occurred in Nix gene sequences were categorized as a point mutation. The change of Nix gene sequences was occurred between the nitrogenous base of guanine to adenine (G>A), thymine to adenine (T>A) and cytosine to adenine (C>A) in certain sequence numbers. There were six and nineteen on the forward-strand and reverse-strand of the Nix gene, respectively, due to ?-irradiation treatment. We conclude that ?-irradiation exposure causes point mutation on the Nix gene of males Ae. aegypti.